Pengembangan Media Komikdigital untuk Meningkatkan Kemampuan Berikir Kritis Peserta Didik Sekolah Dasar pada Mata Pelajaran Bahasa Indonesia Kelas III - Ayu, Aan Naisya Tri; Wahyudi, Wahyudi (Universitas Syiah Kuala, 2025)
This study aims to develop a digital comic media as a practical and engaging learning tool to improve critical thinking skills of third-grade elementary students in the subject of Indonesian language, specifically in the interview material. The research was motivated by the limited use of interactive and relevant learning media suitable for elementary school characteristics, hence the need for innovative media to enhance students' engagement and understanding. The research method used is Research and Development (RD) with a simplified Borg Gall development model. The subjects of this study were third-grade students at SD Negeri Sumberejo 01. Data collection techniques used questionnaires to measure the responses and effectiveness of the developed media. The results showed that the developed digital comic media received highly positive responses from both students and teachers. The media was considered interesting, easy to use, and helpful in enhancing students understanding of interview material. Furthermore, the use of digital comics in learning was proven to support the development of students' critical thinking through observation and content comprehension. Thus, it can be concluded that digital comic media is feasible to be used as an alternative learning tool for Indonesian language instruction in elementary schools.